Health Analysis of the Five Largest Banks in Indonesia during Global Uncertainty Using the RGEC Method: (Case Study on Bank Mandiri, BRI, BCA, BNI, and BTN for the Period 2020-2024) - Vika Diyah Ardiyanti; Arisha Putri Pradita (Admisi dan Bisnis, 2025)
Various countries are facing diverse and complex challenges in recent years. This certainly has an impact on the banking industry. This study aims to analyze the health level of the five banks with the largest assets in Indonesia in the period 2020 to 2024 using the RGEC method. The results of the study show that during the period 2020-2024, Bank Mandiri, BRI, and BCA received the predicate "very healthy" which means they are considered "very capable" of facing changes in business conditions and other external factors. BNI received the predicate "healthy" in the period 2020, but increased to "very healthy" in the period 2021 to 2024. However, overall, BNI bank received the predicate "very healthy". BTN received the predicate "healthy" during 2020 to 2025, which means it is considered "capable" of facing changes in business conditions and other external factors.   Berbagai negara sedang menghadapi tantangan yang beragam dan kompleks beberapa Year terakhir.  Hal tersebut tentunya berdampak terhadap industri perbankan. Penelitian ini bertujuan menganalisis tingkat kesehatan lima bank dengan asset terbesar di Indonesia pada periode 2020 sampai 2024 menggunakan metode RGEC. Hasil penelitian menunjukkan bahwa selama periode 2020-2024, Bank Mandiri, BRI, dan BCA memperoleh predikat “sangat sehat” yang berarti dinilai “sangat mampu” menghadapi perubahan kondisi bisnis dan faktor eksternal lainnya. BNI memperoleh predikat “sehat” pada periode 2020, namun meningkat menjadi “sangat sehat” pada periode 2021 sampai 2024. Namun secara keseluruhan, bank BNI memperoleh predikat “sangat sehat”. BTN memperoleh predikat “sehat” selama 2020 sampai dengn 2025,  yang berarti dinilai “mampu” menghadapi perubahan kondisi bisnis dan faktor eksternal lainnya.